Germany's Poor Economic Performance in the Last Decade: It's the Macroeconomy, not Institutional Sclerosis - Achim Truger (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2003)
This paper challenges the institutional sclerosis explanation of the German crisis according to which rigid labour markets and generous welfare state institutions have driven Germany into its position as "Europe's sick man". In general, the explanation is not convincing, because the underlying hypotheses about the effects of labour market regulation and welfare state institutions on employment and growth cannot unambiguously be derived from modern labour market theory and are at least partially at odds with accepted empirical findings. In particular, the explanation is unconvincing, because in international comparison Germany's labour market and welfare state institutions are simply not as sclerotic as often supposed. In most of the aggregate indicators for structural rigidities Germany is not worse than the average OECD or EU country. Moreover, there is a macroeconomic explanation focusing on the combined effects of restrictive and procyclical monetary, fiscal and wage policy in Germany that is broadly consistent with mainstream macroeconomics and is well backed by empirical data.
Keywords: 330